The Ethical Dilemma in Globalising Small Businesses - Nganga , Jacob C. (Journal of Law and Governance, 2012)
This paper is largely a theoretical exposition of ethical challenges that stifle the participation of small businesses in the global value chains with particular reference to businesses in developing countries. Smallbusiness clusters in developing economies, remain locked in low-quality products and low-income markets. With little innovation, small business lack capacity to produce goods that can attract foreign demand. Yet, small enterprises must provide productive employment for an increasing number of job-seekers in these countries. Innovation growth in small enterprises is normally limited to apprenticeship process and as such, results in a dead-end to progress of indigenous technology. To promote creation and growth of small business, efforts are required to put the small business clusters in a global value chain as this enhances possibilities of new market avenues and as well as benching market indigenous innovative efforts to international standards. Exposure of small business to global market also encourages networks formations which are conduits of skills for quality improvement and valuation of products from the sector. However, the quest for improving the participation and market share of small business is faced with challenges that stem from the way the process of globalization has taken place over time. To overcome these globalization challenges, policy makers must contend with ethical issues that require to be addressed through consultative efforts at international arena.